Does the Immediacy of Feedback Matter in Game-Based Classroom Management? Analysis of the Caught Being Good Game With Adolescent Students. (July 2022) - Bohan, Clare; McDowell, Claire; Smyth, Sinéad
This study evaluated use of the Caught Being Good Game (CBGG) across two adolescent student populations, maintaining a focus on the provision of feedback during the game. The CBGG, a variation of the group contingency intervention the Good Behavior Game (GBG), is a classroom management intervention that involves the provision of points to teams of students who follow class rules. Feedback was manipulated during the game to ascertain whether immediate visual feedback was always necessary. The CBGG was presented with and without immediate visual feedback across phases, using a multiple treatment reversal design. Intervention conditions were counterbalanced across two classrooms of mainstream adolescent students. Data were collected on academically engaged and disruptive behaviors. The CBGG was generally effective in targeting these behaviors in both classrooms, with some differential effects apparent for CBGG versions across classrooms. This provides further support for the use of the CBGG as a positive classroom management technique and as an alternative to the classic GBG. The findings also suggest that teachers may choose whether to use feedback or not during the CBGG, which may save them time and increase buy-in by incorporating an opportunity for some autonomy in game implementation.